Analysis Of Normal Stress Distribution Of Earthquakes In The Fault Segment Of The West Sumatra Region Using The Stress Inversion Method: English - Daya, Ellen Kurniawati; Syafriani, Syafriani; Hamdi , Hamdi; Amir, Harman (Journal of Experimental and Applied Physics, 2024)
West Sumatra was one of the regions on the island of Sumatra that had a high level of earthquake proneness. There were five segments of the Sumatran fault in this region. Normal stress distribution analysis could be carried out to determine tectonic activity in earthquake-prone areas. This research used the stress inversion method to identify normal stresses, which could trigger or inhibit fractures. The data used involved 17 fault plane parameters (strike, dip, rake) from earthquakes with a magnitude of ≥4.7 that occurred in the West Sumatra region from 1967-2023. The type of fault analysed was strike-slip, and the earthquake's epicenter was located on land. The results of this research provided an overview of the position and direction of normal stress due to earthquakes in the West Sumatra region. The distribution of the normal stress position of the fault segment was shown through the pressure and tension axes (P/T), with respectively sigma1, sigma2, and sigma3 having azimuth/plunge values of 353.990/4.760, 247.260/73.860, and 85.310/15.380. The direction of maximum normal stress (sigma1) is spreading in the northern part of the fault segment. In contrast, intermediate normal stress (sigma1) is situated in the western sector of the fault segment, while minimum normal stress (sigma3) is in the eastern part of the fault segment in this region. Analysis of the normal stress distribution is showing that the Talamau segment is being dominated by maximum normal stress, indicating that the Pasaman area and its surroundings are being considered vulnerable to faults and earthquakes.